Penelitian Transformasi Makna Kata Serapan Bahasa Arab Pada Bahasa Indonesia Dalam Istilah Agama Islam dari Aspek Bahasa dan Budayanya: Transformasi Makna Kata Serapan Arab-Indo, Perubahan Makna, Transformasi Makna Pada Istilah-Istilah Agama Islam - Fauzan Hakami; Muaz Kalimatun Nabil; Maghrevian Ramadhany; Laka Zikra; Subhan Khoiri Rahman (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2023)
This research aims to describe Arabic loan words in Indonesian which focuses on terms contained in the Islamic religion and analyze changes in meaning based on linguistic and cultural factors of the source language. This research uses a qualitative descriptive research approach, namely the Systematic Literature Review method with a number of research objects. The data sources used include previous research articles and journals that examine the transformation of language meaning. The research results identified three types of meaning changes in Arabic vocabulary that were adopted into Indonesian. The three types of meaning changes include broad meaning changes, narrowed meaning changes, and total meaning changes. This research provides in-depth insight into how words in Arabic interact with the Islamic religion and are then absorbed into Indonesian, and how these meanings change over time and context in aspects of language and culture.